On the concept of embedded resonators for passive vibration control of tyres. (July 2021) - Errico, F; Petrone, G; Rosa, S De; Franco, F; Ichchou, M
An investigation is carried out on structure-borne vibrations of tyre models at low frequencies. The idea is to use embedded resonant meta-materials to damp the tyres' vibrations and thus reduce the transferred energy to the main attached structures. A simplified tyre model is used, being the investigation of the effects of the embedded substructures the main target of the work; internal pressure and tyre rotation effects are neglected at this stage. Different configurations are tested targeting different natural modes of the tyre, while mechanical excitation is assumed on one section of the tyres. The results show how the proposed designs open new possible and feasible solutions for the vibration control.